2015
DOI: 10.18632/oncotarget.3539
|View full text |Cite
|
Sign up to set email alerts
|

miR-181c associates with tumor relapse of high grade osteosarcoma

Abstract: High-grade osteosarcoma (OS) is characterized by low incidence, high aggressiveness and moderate 5-years survival rate after aggressive poly-chemotherapy and surgery. Here we used miRNA profiling as a tool to possibly predict and monitor OS's development and therapeutic outcome. First, we evaluated the altered expression of selected miRNAs from a case of Giant Cell Tumor (GCT) apparently evolved into an OS. We found that most of modulated miRs were associated with pathways of bone resorption and osteogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…We previously demonstrated that HCV transcriptionally down‐regulates miR‐181c expression . Suppression of miR‐181c may be a prognostic indicator in rapidly proliferating cells, like glioblastoma, osteosarcoma, and ovarian carcinoma . Multiple molecules act as targets for miR‐181c, including Six2 in metanephric mesenchymal cells, FoxO1 in diabetic endothelial cells, transforming growth factor β in glioblastoma cells, PRKCD in ovarian cells, and Erk in prostate cancer cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that HCV transcriptionally down‐regulates miR‐181c expression . Suppression of miR‐181c may be a prognostic indicator in rapidly proliferating cells, like glioblastoma, osteosarcoma, and ovarian carcinoma . Multiple molecules act as targets for miR‐181c, including Six2 in metanephric mesenchymal cells, FoxO1 in diabetic endothelial cells, transforming growth factor β in glioblastoma cells, PRKCD in ovarian cells, and Erk in prostate cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…(16) Suppression of miR-181c may be a prognostic indicator in rapidly proliferating cells, like glioblastoma, osteosarcoma, and ovarian carcinoma. (33)(34)(35) Multiple molecules act as targets for miR-181c, including Six2 in metanephric mesenchymal cells, FoxO1 in diabetic endothelial cells, transforming growth factor β in glioblastoma cells, PRKCD in ovarian cells, and Erk in prostate cancer cells. (35)(36)(37)(38)(39) Here, we focused on the functional importance of miR-181c down-regulation in HCV-infected hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…There is another report that the loss of miR-181a-1/b-1 dampens the induction of experimental autoimmune encephalomyelitis and reduces basal TCR signaling in peripheral T cells and their migration from lymph nodes to pathogenic sites [ 23 ]. miR - 181c inhibits glioblastoma cell invasion, migration and mesenchymal transition by targeting the TGF-beta pathway and is associated with metastatic brain cancer and high-grade osteosarcoma [ 24 26 ]. miR - 181d acts as a glioma suppressor by targeting K-ras and Bcl-2 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide strong evidence that manipulating the functions of specific miRNAs might be a promising approach in tumor therapy. Evidence from previous studies showed that miR-181c correlated with high grade OS recurrence, enhancing chemotherapeutic-induced cell death and reducing cell viability [11]. Therefore, in this study, we aimed to elucidate the molecular mechanism in the regulations of OS with a focus on miR-181c.…”
Section: Introductionmentioning
confidence: 99%